OP0263 Trans-ancestral meta-analysis identifies 13 new loci associated with serum urate levels. (15th June 2017) - Merriman, TR; Cadzow, M; Topless, R; Mount, D; Choi, H; Okada, Y; Boocock, J; Stahl, E
Abstract : Background: Serum urate is an important biomarker for gout disease and kidney function. Genome-wide association study (GWAS) meta-analyses have identified 28 loci in European and East Asian population samples. Combined analysis of these summary data across populations offers the opportunity to discover new serum urate associations through greater sample size and power, and trans-ancestral analyses provide the opportunity for fine-mapping associations with greater resolution given differing linkage disequilibrium patterns between populations. Objectives: To conduct a meta-analysis of European and East Asian serum urate GWAS. Methods: Summary statistics from European (N=110, 238) (Kottgen et al. 2013) and east Asian (N=21, 268) (Okada et al. 2012) meta-analyses were obtained. We used ImpG v1.0 to impute the results into 1000 Genomes phase 3 variants, and performed sample-size weighted z-score meta-analysis. Linkage-disequilibrium (LD)-independent variants with PMETA < 5x10–8, not in LD (r2<0.1) with previously identified regions, were considered novel serum urate loci. We used functional partitioned LD score regression on all associated loci in the European GWAS to identify SNP-heritability enriched tissue-specific regulatory regions, for use as functional priors in PAINTOR fine mapping analyses to identify putative causal variants. Results: The trans-ancestral meta-analysis of European and East Asian GWAS revealed nine new serum urate-associated loci (PMETA <5x10 -8 ). Three of the new loci are located in the 11q12.3–13.2 region near the established SLC22A11/12 locus. Additional novel loci are located near the FGF5, LNC00603, HLA-DQB1, B4GALT1, BICC1 and USP2 genes. Tissue-focused functional partitioning of SNP-heritability indicated the strongest enrichments of kidney, GI and liver tissues (P<10 -7 ), among other significant tissues. Trans-ancestral meta-analysis and functional fine-mapping decreases the numbers of SNPs in causal variant credible sets, and for example pinpoints the rs17632159 SNP as likely causal (posterior P>0.9) at the TMEM171/174 locus. Conclusions: Meta-analysis of existing GWAS increases power and leads to the identification of nine new loci associated with serum uric acid levels. Increased resolution in trans-ancestral GWAS, with functional annotation enrichments, improves fine-mapping of serum urate GWAS loci. References: Köttgen A, et al. Genome-wide association analyses identify 18 new locis associated with serum urate concentrations. Nature Genet. 2013;45:145–54. Okada Y, et al. Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. Nature Genet. 2012;44:904–9. Disclosure of Interest: None declared